2018
DOI: 10.1002/cbin.11039
|View full text |Cite
|
Sign up to set email alerts
|

FMRP regulates endothelial cell proliferation and angiogenesis via the miR‐181a‐CaM‐CaMKII pathway

Abstract: RNA binding proteins (RBPs) and microRNAs have emerged as crucial post-transcriptional regulators of gene expression. Although the role of Fragile X mental retardation protein (FMRP) has been well studied in the brain, the function of FMRP in endothelial cells remains unknown. In our study, we showed that FMRP controlled human umbilical vein endothelial cells (HUVECs) proliferation and angiogenesis via the miR-181a-mediated calmodulin (CaM)/CaMKII pathway. The knockdown of FMRP induced miR-181a expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Interestingly, this protein is a tumor suppressor with angiogenic properties, as demonstrated in rat 3Y1 cells transformed with v-src by reducing VEGF expression, and hence cell proliferation and cell motility [214]. Finally, in connection with the function of CaM in angiogenesis it is worth mentioning that the anti-angiogenic action of TNF-α is due to FMRP (fragile X chromosome mental retardation protein) dephosphorylation, facilitating in this manner the expression of miR-181a, a microRNA that blocks CaM translation, therefore preventing CaMK-II activation [215].…”
Section: Calmodulin-regulated Proteins In Cell Invasion and Metastasismentioning
confidence: 98%
“…Interestingly, this protein is a tumor suppressor with angiogenic properties, as demonstrated in rat 3Y1 cells transformed with v-src by reducing VEGF expression, and hence cell proliferation and cell motility [214]. Finally, in connection with the function of CaM in angiogenesis it is worth mentioning that the anti-angiogenic action of TNF-α is due to FMRP (fragile X chromosome mental retardation protein) dephosphorylation, facilitating in this manner the expression of miR-181a, a microRNA that blocks CaM translation, therefore preventing CaMK-II activation [215].…”
Section: Calmodulin-regulated Proteins In Cell Invasion and Metastasismentioning
confidence: 98%
“…A complete gene analysis showed that cell cluster #9 upregulated several known pro-angiogenic genes and transcription factors that are expressed in mesenchymal stromal cells (Sca-1/Ly6A, Ccl2, Ankrd1, Nfe2l1; Figures 4 H–4K and S7 ). 28 , 29 , 30 In addition, we saw elevated Fmr1, which regulates endothelial cell proliferation and angiogenesis, 31 and higher Zc3 h15 expression that correlates with expression of the pro-angiogenic protein a-fetoprotein (AFP). 32 , 33 Taken together, these results suggest the 7G-modRNA cocktail’s beneficial mechanism of action may occur via angiogenesis and paracrine effects to induce cardiovascular regeneration post MI.…”
Section: Resultsmentioning
confidence: 91%
“…There is also evidence that miRNAs play a regulatory role in aberrant CaM/CaMKII cascades in ischemia and reperfusion. For example, miR-181a has been shown to participate in the CaM/CaMKII pathway during the action of the Fragile X mental retardation protein in controlling the proliferation and angiogenesis of human umbilical vein endothelial cells ( 32 ). CaM and CaMKII expression is affected at the post-transcriptional level by miR-26b ( 33 ), miR-145 ( 34 ), and miR-148a ( 35 ), thereby contributing to the progression of ischemic injury.…”
Section: Introductionmentioning
confidence: 99%